The Fate Status of Stem Cells in Diabetes and its Role in the Occurrence of Diabetic Complications - Xu, Jinyi; Zuo, Chengguo (Frontiers in Molecular Biosciences, 2021)
Diabetes mellitus (DM) is becoming a growing risk factor for public health worldwide. It is a very common disease and is widely known for its susceptibility to multiple complications which do great harm to the life and health of patients, some even lead to death. To date, there are many mechanisms for the complications of diabetes, including the generation of reactive oxygen species (ROS) and the abnormal changes of gas transmitters, which ultimately lead to injuries of cells, tissues and organs. Normally, even if injured, the body can quickly repair and maintain its homeostasis. This is closely associated with the repair and regeneration ability of stem cells. However, many studies have demonstrated that stem cells happen to be damaged under DM, which may be a nonnegligible factor in the occurrence and progression of diabetic complications. Therefore, this review summarizes how diabetes causes the corresponding complications by affecting stem cells from two aspects: stem cells dysfunctions and stem cells quantity alteration. In addition, since mesenchymal stem cells (MSCs), especially bone marrow mesenchymal stem cells (BMMSCs), have the advantages of strong differentiation ability, large quantity and wide application, we mainly focus on the impact of diabetes on them. The review also puts forward the basis of using exogenous stem cells to treat diabetic complications. It is hoped that through this review, researchers can have a clearer understanding of the roles of stem cells in diabetic complications, thus promoting the process of using stem cells to treat diabetic complications.